Análisis de los procesos constructivos en las actividades de chorrea, encofrado y desencofrado de muros y columnas en el proyecto QBO Skyhomes de la empresa H Solís. - Quirós-Robles, Virgina (Instituto Tecnológico de Costa Rica, 2016)
The issue of productivity in construction in Costa Rica has been in progress over time but still lack knowledge about it. It is worth mentioning that not only sufficient for a process to be executed quickly, since it must have a comprehensive balance between runtimes and quality of the final product to achieve benefits both economy and on time. This project has as principal objective the analysis and improvement of the construction process of placing concrete in walls and columns and the placing and the removing of formwork in the same elements, in the QBO Skyhomes project of the construction company H Solís. To achieve evaluating the productivity they were used the method of Work Sampling and Crew Balance making thirty-six samples. Although To assess productivity, methods like "Work Sampling" and "Crew Balance" were used, making a total of 36 samples . Besides obtaining yields of the processes, took place an improvement proposal developed based on negative factors found and process control templates such as: concrete placing, placing and removing formwork, in walls and columns. Among the most striking findings was the determination of, what factors were affecting the productivity and performance of the activities studied, such as delays in concrete arrivals, inadequate size of crew, problems with crane time planning and lack of a lift for loading of materials and people within the project. Control templates proposed were assessed for a period of one week in removing formwork, in which assessed the quality of the walls that had been worked. Thus it was concluded broadly that the walls had been evaluated with an "'Optimal criteria".
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2016.
Keywords: Productividad; Mano de Obra; Rendimiento; Sistemas de control; Construcción